2013
DOI: 10.3892/mmr.2013.1504
|View full text |Cite
|
Sign up to set email alerts
|

miR-203 regulates the proliferation, apoptosis and cell cycle progression of pancreatic cancer cells by targeting Survivin

Abstract: MicroRNAs have emerged as crucial regulators of tumorigenesis. However, the mechanism by which miR‑203 is involved in the pathogenesis of pancreatic cancer (PC) remains elusive. In the present study, PC cell lines were used as an experimental model to investigate the expression and functional role of miR‑203 in PC. miR‑203 mimic virus, miRNA negative control virus and Survivin shRNA virus were transfected into the PC cell line, CFPAC‑1. mRNA and protein levels of Survivin were detected using qPCR and western b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 28 publications
1
38
0
Order By: Relevance
“…Mechanistically, it was demonstrated that miR-96 imparted its effect by inhibiting K-RAS and Akt signaling [26]. In a recent study, Xu et al [27] demonstrated the potential of miR-203 in the inhibition of Survivin, which is overexpressed in majority of cancers, including pancreatic cancer and plays a role in cytoprotection, apoptosis resistance and cell-cycle regulation. Their study showed that overexpression of miR-203 effectively induced apoptosis, inhibited cell proliferation and caused cell cycle arrest.…”
Section: Biological Significance Of Mirnas In Pancreatic Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanistically, it was demonstrated that miR-96 imparted its effect by inhibiting K-RAS and Akt signaling [26]. In a recent study, Xu et al [27] demonstrated the potential of miR-203 in the inhibition of Survivin, which is overexpressed in majority of cancers, including pancreatic cancer and plays a role in cytoprotection, apoptosis resistance and cell-cycle regulation. Their study showed that overexpression of miR-203 effectively induced apoptosis, inhibited cell proliferation and caused cell cycle arrest.…”
Section: Biological Significance Of Mirnas In Pancreatic Cancermentioning
confidence: 99%
“…Their study showed that overexpression of miR-203 effectively induced apoptosis, inhibited cell proliferation and caused cell cycle arrest. Furthermore, in vivo study also demonstrated a potent effect of miR-203 on tumor growth inhibition [27]. Farhana et al [28] provided evidence that modulation of miR-150* and miR-630 expression resulted in diminished cellular growth and induced apoptosis.…”
Section: Biological Significance Of Mirnas In Pancreatic Cancermentioning
confidence: 99%
“…The same effect is attributed to miR-34a in pancreatic cells [136]. miR-203 overexpression inhibited pancreatic cell proliferation [137] and tumour growth in a mouse model [138]. miR-17-92 is an oncogenic cluster [139,140,141], but also a tumour suppressor [142].…”
Section: Dietary Phytochemicals As Non-coding Genes Regulatorsmentioning
confidence: 99%
“…Survivin has little or no expression in normal cells but has high expression in a variety of tumor cells. Survivin is a specific target molecule of miR-203 [20]. After transfecting miR-203, the expression of survivin will be downregulated, which will induce cell apoptosis, inhibit cell proliferation, and reduce tumor invasion [21].…”
Section: Mirnas Inhibit Laryngeal Cancer Cell Proliferationmentioning
confidence: 99%
“…However, the molecular mechanism of laryngeal cancer is still unclear. MicroRNA (miRNA) is a small molecule non-coding RNA with a length of about [19][20][21][22][23][24][25] nucleotides that regulates gene expression by binding to messenger RNA, leading to transcript degradation or translational inhibition [9]. Bioinformatics analysis predicts that miRNA regulates more than 30% of protein-coding genes.…”
mentioning
confidence: 99%